Penerapan Pendekatan Saintifik untuk Meningkatkan Pemahaman Konsep dan Praktik Sholat Jumat - inayatu Khoirul Magfiroh (Institut Agama Islam Uluwiyah Mojokerto Indonesia, 2025)
The low level of conceptual understanding and practical performance of Friday Prayer (Ṣalāt al-Jumu‘ah) among third-grade students presents a challenge in Fiqh instruction, which requires mastery of cognitive as well as psychomotor and affective domains. This study aims to improve students’ conceptual understanding and practical implementation of Friday Prayer through the application of a scientific approach in Fiqh learning. The research employed a Classroom Action Research (CAR) design, conducted cyclically through the stages of planning, action implementation, observation, and reflection. The scientific approach was applied through activities of observing, questioning, collecting information, reasoning, and communicating the material on Friday Prayer in a contextual and participatory manner. Research data were obtained from learning activities, teachers’ reflective notes, as well as the responses and engagement of third-grade students at MI Mambaul Ulum Terik, Sidoarjo, during the implementation of the actions. The research subjects were students in the Fiqh subject at a faith-based educational institution, which served as the research setting. The expected findings indicate that the implementation of the scientific approach can enhance the quality of the Fiqh learning process, strengthen students’ conceptual understanding, and develop meaningful and sustainable practical skills in performing Friday Prayer, thereby contributing to impactful learning. Rendahnya pemahaman konsep dan praktik Sholat Jumat pada peserta didik kelas tiga menjadi tantangan dalam pembelajaran Fiqih yang menuntut penguasaan aspek kognitif sekaligus psikomotorik dan afektif. Penelitian ini bertujuan untuk meningkatkan pemahaman konsep dan praktik Sholat Jumat melalui penerapan pendekatan saintifik dalam pembelajaran Fiqih. Penelitian menggunakan desain Penelitian Tindakan Kelas (PTK) dengan tahapan perencanaan, pelaksanaan tindakan, observasi, dan refleksi yang dilaksanakan secara siklikal. Pendekatan saintifik diterapkan melalui aktivitas mengamati, menanya, mengumpulkan informasi, menalar, dan mengomunikasikan materi Sholat Jumat secara kontekstual dan partisipatif. Sumber data penelitian diperoleh dari aktivitas pembelajaran, hasil refleksi guru, serta respons dan keterlibatan peserta didik kelas tiga di MI Mambaul Ulum Terik Sidoarjo, selama proses tindakan berlangsung. Objek penelitian adalah peserta didik pada mata pelajaran Fiqih di satuan pendidikan menengah berbasis keagamaan sebagai lokus riset. Arah temuan penelitian diharapkan menunjukkan bahwa penerapan pendekatan saintifik mampu meningkatkan kualitas proses pembelajaran Fiqih, memperkuat pemahaman konseptual, serta mengembangkan kemampuan praktik ibadah Sholat Jumat secara bermakna dan berkelanjutan, sehingga berkontribusi pada penguatan pembelajaran berdampak.